Die einde van die moraal? "n Beginning oor die lotgevalle van die moraal in die (post)moderne samelewing - Schoeman, Marinus (HTS teologiese studies, 2001)
The end of morality? Reflections on the fate of morality in (post)modern society. True morality, so it is argued, relates to a sense of reality. This implies an openness towards the Other, towards that which transcends our own subjectivity, our emotions or sentiments, and our desires. Morality is always oriented towards transcendence. By this standard, the "thin" or minimalist morality which is nowadays acclaimed as the only legitimate form of morality in pluralistic or multicultural societies is no morality in the true (real) sense of the word. The idea of a "thin" morality leads to a sentimentalist and narcissistic concept of the self, which is indicative of a serious impoverishment in, or indeed the end of, morality as such. Ethical reflection should take account of this situation. Although we cannot simply return to traditional forms of morality, we should nevertheless acknowledge that they could still have an important heuristic value in moral practice. There are several traditions (inter alia the Christian tradition) that merit thorough hermeneutic inquiry, and this in turn could perhaps ofer a way out of the current impasse in which morality inds itself.